2017
DOI: 10.1007/s11136-017-1667-5
|View full text |Cite
|
Sign up to set email alerts
|

Subjective evaluation of psychosocial well-being in children and youths with overweight or obesity: the impact of multidisciplinary obesity treatment

Abstract: In a large group of children and youths, psychosocial well-being improved during a multidisciplinary childhood obesity treatment programme, irrespective of the degree of obesity at treatment entry. Greater reductions in BMI SDS were associated with greater improvements in psychosocial well-being, but even in the group increasing their BMI SDS improvements were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 55 publications
2
22
0
Order By: Relevance
“…The TCOCT intervention is used in the treatment of children with obesity in Denmark and our results ad to previous ndings [4], by including long-term follow-up in children who were more obese and younger. Fonvig et al reported bene cial changes in 5 out of 6 VAS-items for children with increasing BMI-SDS.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The TCOCT intervention is used in the treatment of children with obesity in Denmark and our results ad to previous ndings [4], by including long-term follow-up in children who were more obese and younger. Fonvig et al reported bene cial changes in 5 out of 6 VAS-items for children with increasing BMI-SDS.…”
Section: Discussionsupporting
confidence: 90%
“…Recently, a 14 months multifactorial lifestyle intervention in children with obesity reported increased QoL, mood, and body satisfaction whereas appetite, bullying, and motivation were decreased. Interestingly, similar positive changes were observed in ve of the six VAS items in the 24.4% of children who increased their Body Mass Index-Standard Deviation Score (BMI-SDS) during the intervention [4]. The aim of our study was to evaluate long-term effects of a comparable multifactorial lifestyle intervention on measures of QoL in children with obesity.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…Furthermore, the present study included a relatively large study population compared with similar previous studies in children, especially in our analyses of intervention outcome. Importantly, the children and adolescents with overweight and obesity underwent treatment using The Children’s Obesity Clinic protocol, which has, in several nonrandomized studies, shown improvement in metabolic risk variables and psychosocial well‐being, including degree of obesity in both patients and their parents , blood pressure , plasma lipid fractions , body composition , liver and muscle fat content , and quality of life .…”
Section: Discussionmentioning
confidence: 99%
“…9,13,25 The reduction in BMI-even moderateobserved during and after the period of care may significantly improve the short-term, mid-term, and long-term health of children and limit the consequences of obesity. 4,5,26 Indeed, recent investigations have shown that a reduction in BMI in children significantly improved hypertension, hypertriglyceridemia, and low HDLcholesterol during adulthood, 26 was associated with greater improvements in their psychosocial well-being, 27 and seemed to be effective in improving the quality of life in the physical, emotional, social, and psychosocial domains. 28 Moreover, the homogeneous outcomes observed confirm the sustainability, transferability, and reproducibility of the multidisciplinary care offered by the French networks and may be considered as a proof of concept of such organisation of care for paediatric obesity.…”
Section: Discussionmentioning
confidence: 99%